Structural insights into the assembly and activation of the IL‐27 signaling complex. (3rd August 2022) - Jin, Yibo; Fyfe, Paul K; Gardner, Scott; Wilmes, Stephan; Bubeck, Doryen; Moraga, Ignacio
Abstract: Interleukin 27 (IL‐27) is a heterodimeric cytokine that elicits potent immunosuppressive responses. Comprised of EBI3 and p28 subunits, IL‐27 binds GP130 and IL‐27Rα receptor chains to activate the JAK/STAT signaling cascade. However, how these receptors recognize IL‐27 and form a complex capable of phosphorylating JAK proteins remains unclear. Here, we used cryo electron microscopy (cryoEM) and AlphaFold modeling to solve the structure of the IL‐27 receptor recognition complex. Our data show how IL‐27 serves as a bridge connecting IL‐27Rα (domains 1–2) with GP130 (domains 1–3) to initiate signaling. While both receptors contact the p28 component of the heterodimeric cytokine, EBI3 stabilizes the complex by binding a positively charged surface of IL‐27Rα and Domain 1 of GP130. We find that assembly of the IL‐27 receptor recognition complex is distinct from both IL‐12 and IL‐6 cytokine families and provides a mechanistic blueprint for tuning IL‐27 pleiotropic actions. Synopsis: Interleukin 27 is a heterodimeric cytokine that elicits potent immuno‐suppressive responses. The structure of the IL‐27 signalling complex provides a mechanistic blueprint to fine‐tune IL‐27 immuno‐modulatory activities. IL‐27 is a heterodimeric cytokine in which EBI3 engages p28 at site 1. IL‐27Rα binds site 2 of p28 and is stabilized by electrostatic interactions with EBI3. Domain 1 of GP130 binds site 3 of p28 in a low affinity interaction. Abstract : Interleukin 27 is a heterodimeric cytokine that elicits potent immuno‐suppressive responses. The structure of the IL‐27 signalling complex provides a mechanistic blueprint to fine‐tune IL‐27 immuno‐modulatory activities.